The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.3390/w7020615
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Fecal Coliform Loads in Urban Watersheds by Hydrologic/Hydraulic Modeling: Case Study of the Beauport River Watershed in Quebec

Abstract: A three-step method for the identification of the main sources of fecal coliforms (FC) in urban waters and for the analysis of remedial actions is proposed. The method is based on (1) The statistical analysis of the relationship between rainfall and FC concentrations in urban rivers; (2) The simulation of hydrology and hydraulics; and (3) Scenario analysis. The proposed method was applied to the Beauport River watershed, in Canada, covering an area of 28.7 km 2 . FC loads and concentrations in the river, durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…This increase in coliforms during the rainy season has been evidenced in several studies, where it is associated with an increase in runoff and wastewater towards the coasts [31]. In addition, this increase in discharges decreases the salinity and increases the temperature of the system, thus favoring bacterial growth [32,33].…”
Section: Discussionmentioning
confidence: 71%
“…This increase in coliforms during the rainy season has been evidenced in several studies, where it is associated with an increase in runoff and wastewater towards the coasts [31]. In addition, this increase in discharges decreases the salinity and increases the temperature of the system, thus favoring bacterial growth [32,33].…”
Section: Discussionmentioning
confidence: 71%
“…In the present study, we also found mean daily inflow (DSF)—collinear in the statistical models with rain events— was also identified as a significant factor affecting not only E. coli concentrations ( p = 0.005), but also presence ( p = 0.0004) (Supplemental Tables S4 and S5). Thériault and Duchesne (2015) also reported a significant relationship between mean fecal coliform concentrations in the Beauport River Watershed in Quebec City, Canada, and the amount of rainfall observed on the same day and on the day before fecal coliform measurement. In addition, Jones et al (2017) reported that surface water flow and higher daily rainfall were the most important variables for broadly delineating detection of human and animal viruses, as well as F ‐specific coliphage—a fecal indicator for viruses.…”
Section: Resultsmentioning
confidence: 83%
“…The authors observed higher concentrations of FIB in urban runoff when compared with agricultural and mixed land use areas. Additionally, runoff water can overload the capacity of municipal sewage systems, resulting in the discharge of untreated water into nearby receiving rivers (McLellan et al, 2007; Thériault and Duchesne, 2015). Historically a greater issue with combined sewer systems, sanitary sewer systems can be affected by infiltration of rainwater through the subsurface into compromised infrastructure (i.e., cracks, broken pipes, equipment failure, blockages), resulting in sanitary sewer overflows (Arnone and Walling, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Microbes in urban stormwater originate from both point and diffuse sources, including those from animal and human faecal pollution [2,5,6]. The urban stormwater runoff can mobilise and transport microbial pathogens from various non-point sources to surface water bodies, such as rivers, lakes and creeks.…”
Section: Introductionmentioning
confidence: 99%